ANALISIS KEANDALAN DAN SUSUT DAYA PENYULANG TABANAN SETELAH REKONFIGURASI - Al Farisi, Salman; Sari Hartati, Rukmi; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 5 No 2 (2018): Jurnal SPEKTRUM, 2018)
The need for electricity in this global era is increasing, so that a more reliable electrical system is needed. A reliable system cannot be separated from interference, so there needs to be a system reliability analysis and power loss to the feeder by configuring the network. This research was conducted to find the reliability index value in the form of interference frequency and duration of interference (SAIFI and SAIDI). In one Tabanan feeder the results obtained exceed the standard so reconfiguration is performed Based on the analysis obtained before reconfiguration, the reliability index for SAIFI is 6,7456 (failure / year) and SAIDI is 11,4767 (hour / year) and power loss by 6,27 %. After reconfiguration of Tabanan feeder, the reliability index was better, for SAIFI is 5.2475 (disturbance / year) and SAIDI is 9,8798 (hour / year), the power loss was 2.82%. Sanggulan feeder is a new feeder reconfiguration result from Tabanan feeder, where the analysis was carried out to find out the reliability index of Sanggulan feeder, it was obtained the SAIFI value of 4.5753 (disturbance / year) and SAIDI of 9.5297 (hour / year) and power loss of 4,80%.